Surfacing rates, swim speeds, and patterns of movement of Antarctic blue whales - Calderan, Susannah V.; Leaper, Russell; Andrews-Goff, Virginia; Miller, Brian S.; Olson, Paula A.; Reyes, M. V. Reyes; Bell, Elanor; Double, Michael C. (Frontiers in Marine Science, 2023)
During three surveys in the austral summers of 2013, 2015, 2019, data on Antarctic blue whale blow rates, dive times, swim speeds, and broadscale movements were collected using video photogrammetric tracking and intra-voyage photo-identification. A total of 24.4 hours of video observations were suitable for blow interval or movement analysis. Similar to other blue whale populations, Antarctic blue whale dive behaviour comprised a sequence of short dives followed by a long dive with a mean dive time for short dives of 17.6 s, and a mean long dive time of 189.3 s. Two separate methods were used to estimate the average blow rate for Antarctic blue whales, giving estimates of 59.7 and 63.2 blows per hour. The overall mean swim speed over the course of all suitable video track segments was 1.59 ms-1, but there were significant differences between years in the mean of the overall movement rate for each track; average movement rates were lower in 2015 compared to 2013 and 2019 (0.90 ms-1, 1.84 and 1.55 ms-1 respectively), with higher rates of turning in 2015. In 2019, there was faster overall movement through the study area in a consistent direction. The total number of photo-identified blue whales re-sighted intra-season in 2013 was nine (out of 50 identified individuals); in 2015 it was seven (out of 46); in 2019 two (out of 25). Whales remained for several days with little overall movement within the 2015 study area, whereas they were moving through the study area in 2019, which would explain the low number of intra-season resights. The predominant heading in 2019 was towards the area of Antarctic blue whale concentrations at the entrance to the Ross Sea observed in previous years. The photo-identification data also show a high proportion of resighted whales with coherent movements. This suggests that Antarctic blue whales might travel together, at least over periods of several days or sometimes up to a month. The differences between behaviours in 2015 and 2019 in particular may be related to differences in the characteristics of krill swarms between the study areas.